Drgania Swobodne i Wymuszone Płyty Trójkątnej - Solecki, R. (Engineering Transactions, 1960)
The author describes investigations of the vibration of a plate representing a half of a regular triangle. In Sec. 2 a plate simply supported on the periphery is considered. The starting point for further solutions are the eigenfunctions (determined for a regular triangle by H. SCHAEFER and A. HAVERS) in the form of infinite series. In Sec. 3 the author derives the equations of frequency for a plate having additional point supports. Numerical results are given. In the Sec. 4 the plate under consideration is a plate with some of or all the edges clamped. The equations of the method of «forces» are represented in the form of FREDHOLM's integral equations of the first kind. In one case the FREDHOLM equation is transformed, for the sake of example, into a system of algebraic equations. A bibliography of the vibration problem of triangular plates is given.